AL-BALAGHAH; ANTARA PENGETAHUAN DAN DISIPLIN ILMU (PERSPEKTIF SEJARAH BAHASA DAN SASTRA ARAB) - Abdul Hamid, M. (Laboratorium Informasi & Publikasi Fakultas Humaniora UIN Maulana Malik Ibrahim Malang, 2008)
At first, the study of al balaghah was focused on the study of al ma’nani, that functions to remove lahn similar with nahwu. The history of al balaghah is divided into four stages, 1) marhalah al-nasy’ah (growth), (2) marhalah al-numuw (development), (3) marhalah al-izdizar (glory), and (4) marhalah al-dhubul (decline). In Jahiliyah era, the Arabs used al fashahah and al balaghah in their language. They were proud much on their language style in orang language, however the al-balaghah was not constructed as a field of knowledge yet. During Bani Ummaya era, there were many khitabaat, asy’ar and natsr contributing to the development al-balaghah as a field of study. Furthermore, in Bani Abbasiyyah era, al balaghah as a field of study was well formed so that mustholahaat on the discussion of balaghah was defined and well ordered. In the following era, al balaghah declined without significant development.